Plasma antibodies from humans infected with zoonotic simian foamy virus do not inhibit cell-to-cell transmission of the virus despite binding to the surface of infected cells. - Mathilde Couteaudier; Thomas Montange; Richard Njouom; Chanceline Bilounga-Ndongo; Antoine Gessain; Florence Buseyne (PLoS Pathogens)
Zoonotic simian foamy viruses (SFV) establish lifelong infection in their human hosts. Despite repeated transmission of SFV from nonhuman primates to humans, neither transmission between human hosts nor severe clinical manifestations have been reported. We aim to study the immune responses elicited by chronic infection with this retrovirus and previously reported that SFV-infected individuals generate potent neutralizing antibodies that block cell infection by viral particles. Here, we assessed whether human plasma antibodies block SFV cell-to-cell transmission and present the first description of cell-to-cell spreading of zoonotic gorilla SFV. We set-up a microtitration assay to quantify the ability of plasma samples from 20 Central African individuals infected with gorilla SFV and 9 uninfected controls to block cell-associated transmission of zoonotic gorilla SFV strains. We used flow-based cell cytometry and fluorescence microscopy to study envelope protein (Env) localization and the capacity of plasma antibodies to bind to infected cells. We visualized the cell-to-cell spread of SFV by real-time live imaging of a GFP-expressing prototype foamy virus (CI-PFV) strain. None of the samples neutralized cell-associated SFV infection, despite the inhibition of cell-free virus. We detected gorilla SFV Env in the perinuclear region, cytoplasmic vesicles and at the cell surface. We found that plasma antibodies bind to Env located at the surface of cells infected with primary gorilla SFV strains. Extracellular labeling of SFV proteins by human plasma samples showed patchy staining at the base of the cell and dense continuous staining at the cell apex, as well as staining in the intercellular connections that formed when previously connected cells separated from each other. In conclusion, SFV-specific antibodies from infected humans do not block cell-to-cell transmission, at least in vitro, despite their capacity to bind to the surface of infected cells. Trial registration: Clinical trial registration: www.clinicaltrials.gov, https://clinicaltrials.gov/ct2/show/NCT03225794/.